Consentement libre et éclairé et les stérilisations imposées de femmes des Premières Nations et Inuit au Québec - Commission de la santé et des services sociaux des Premières Nations du Québec et du Labrador; Basile, Suzie; Bouchard, Patricia (2022)
La présente recherche vise à pallier le manque de données sur la stérilisation imposée de femmes des Premières Nations et Inuit au Québec. Il s’agit d’une occasion unique pour les femmes des Premières Nations et Inuit au Québec de faire connaître leur histoire et de témoigner dans un cadre respectueux des principes de recherche avec les peuples autochtones (Asselin et Basile, 2012). À notre connaissance, aucune étude n’a encore été menée sur le sujet au Québec, si bien que ce projet semble tout à fait inédit et permet de répondre à un réel besoin de faire avancer la recherche sur cette problématique. Dans cette intention, la recherche sur la stérilisation imposée des femmes des Premières Nations et Inuit permet de mettre en lumière les enjeux sous-jacents de cette problématique. Ainsi, la notion de consentement libre et éclairé est au coeur de la recherche, tout comme l’étude du racisme et de la discrimination systémique vécue par les femmes autochtones au sein du système de santé.
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; canada; cours; discipline; droits des femmes*; intersectionnalité; justice reproductive; maternité; pol4102; premier cycle; périodes historiques; québec; recherche avec les peuples autochtones; régions géographiques; santé; sciences humaines; sciences sociales; sex2283; sexisme; système colonial; systèmes d'oppressions; thématiques; études autochtones

Associations between perceived discrimination and contraceptive method use: why we need better measures of discrimination in reproductive healthcare - Loder, Charisse; Hall, K.; Kusunoki, Yasamin; Harris, Lisa Hope; Dalton, Vanessa (Women & Health, 2021)
Discrimination has historically contributed to coercive contraceptive in the United States. We investigated associations between perceived discrimination, or the perception of unequal treatment in everyday life, and contraceptive method use among U.S. women. We analyzed population-based data from a 2013 study of U.S. women who were premenopausal, age 18–50, sexually active with a male partner in the last year and were not attempting pregnancy. Perceived discrimination was measured using the Everyday Discrimination Scale. Contraceptive method use was categorized into five method categories: permanent, highly effective reversible, moderately effective, barrier and no method. We analyzed relationships between perceived discrimination and contraceptive method use with several regression models, controlling for covariates. Among 539 women in our analytic sample, those with high perceived discrimination had lower incomes, less educational attainment and were less likely to be insured. Perceived discrimination was associated with a reduced odds of using any contraceptive method (aOR 0.43, CI 0.21–0.87, p < .001). Contraceptive method users with high perceived discrimination had an increased odds of using highly effective reversible methods versus moderately effective methods (aOR 5.28, CI 1.63–17.07 p = < .001). Women who perceived discrimination were at risk for contraceptive nonuse; however, among contraceptive users, perceived discrimination was associated with the use of more effective reversible methods.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; contraception; cours; discipline; discriminations; intersectionnalité; inégalités; justice reproductive; médecine; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; santé; sciences; sex2283; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis

Genre, féminismes et développement: une trilogie en construction - Levy, Charmain; Martinez, Andrea (Collection "Études en développement international et mondialisation.", 2019)
Cet ouvrage pédagogique multidisciplinaire conçu pour les cours de premier cycle présente les principaux enjeux théoriques et pratiques de l'heure en matière de genre, féminismes et développement. Misant sur la capacité d'agir et le pouvoir de transformation sociale des femmes des Suds, ce livre examine les enjeux du genre et du développement. Ce manuel féministe, clair et facile à consulter, est spécifiquement conçu pour les cours de premier cycle universitaire sur les femmes, le genre et le développement international. Organisé en sept sections, il offre un panorama aussi vaste que possible des préoccupations féministes reliées au genre et au développement, alimentant ainsi les réflexions et les études de cas dans le domaine. Issu du colloque « État des lieux sur les perspectives féministes en développement international » du Congrès international des recherches féministes dans la francophonie (CIRFF), l'ouvrage propose des contributions de professeures-chercheuses et de militantes européennes, canadiennes et des Suds dédiées à l'avancement des connaissances féministes, à leur diffusion plus large et à leur vulgarisation. Publié en français
Keywords: afro-féminisme; approches et analyses; care; corps; cours; discipline; droits des femmes*; féminisme décolonial; féminisme postcolonial; histoire et politique; intersectionnalité; justice reproductive; outils; ouvrages de références; pol4022; premier cycle; ressource en ligne; santé; science politique; science politique et droit; thématiques; travail; violences; violences sexistes et sexuelles

The Black feminist spatial imagination and an intersectional environmental justice - Ducre, Kishi Animashaun (Environmental Sociology, 2018)
Starting with seminal work from Katherine McKittrick and Katherine McKittrick and the late Clyde Woods, this paper compares and contrasts articulations of justice as espoused by Black feminism, ecofeminism, and the movement for environmental justice. The utilization of an intersectional genealogical approach allows for examination of the ways in which these movements might serve as the ideological bases for a Black feminist spatial imagination and an intersectional environmental justice. A Black feminist spatial imagination is an orientation that accounts for the merger of frames around race, gender, and ecology; it serves as a unique departure from conventional Black feminist analysis by its particular attention to the construct of space in Black feminist epistemology. Analysis reveals that manifestos engage similar strategies around boundedness, an identification among a collective identity and the subject of reproductive justice and liberation as wresting control and self-determination of physical bodies. The final task is an outline of essential tenets for a singular notion of justice of a Black feminist spatial imagination which incorporates the spirit of all of three manifestos and expands current environmental justice discourse to include those ‘who know no one knows’ while highlighting Black women’s agency in environmentally degraded environments. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: afro-féminisme; amériques; approches et analyses; corps; environnement; féminismes noirs; intersectionnalité; justice environnementale; justice reproductive; projet charge mentale; régions géographiques; thématiques; écoféminisme; états-unis

Le territoire comme lieu privilegie de transmission des savoirs et des valeurs des femmes Atikamekw - Basile, Suzy; Asselin, Hugo; Martin, Thibault (Recherches Feministes, 2017)
L’analyse thématique de 32 entrevues réalisées avec des femmes Atikamekw révèle qu’elles connaissent le mode de vie de leurs ancêtres et le rôle que les femmes y jouaient, que ce rôle était prédominant et essentiel dans l’organisation spatiale des activités traditionnelles sur le territoire, que les accouchements sont des marqueurs spatiotemporels, que la désignation du lieu d’origine a changé à la suite des bouleversements sociaux et territoriaux, que la désignation des personnes par le nom traditionnel est toujours en usage, que les femmes Atikamekw étaient responsables de l’éducation. L’obligation d’envoyer les enfants dans les pensionnats de 1955 à 1972 a provoqué une cassure dans la transmission des savoirs sur le territoire et les différentes formes de colonisation ont érodé peu à peu l’influence des femmes.
Keywords: amériques; approches et analyses; canada; care; corps; cours; féminisme autochtone; histoire et politique; intersectionnalité; justice reproductive; justice sociale; maternité; nation Atikamekw; pensionnats; pol4105; premier cycle; québec; régions géographiques; système colonial; systèmes d'oppressions; thématiques; transmissions; violences; éducation

Continuités et ruptures dans le mouvement féministe québécois francophone pour des droits sexuels et reproductifs - Jacquet, Caroline; Pagé, Geneviève; Pirotte, Magaly (Nouvelles Questions Féministes, 2017)
Cet article analyse différents moments du mouvement québécois francophone en faveur de la santé et des droits sexuels et reproductifs à travers le prisme analytique de la justice reproductive. Il s'articule autour de deux critiques développées à l'encontre du mouvement mainstream pro-choix étatsunien, soit la focalisation sur l'avortement et l'absence d'intégration d'une analyse complexe de l'imbrication des rapports de pouvoir déterminant les différentes limites auxquelles font face les femmes en matière de santé et de droits sexuels et reproductifs. À l'opposé d'un schéma historique linéaire, il brosse un portrait nuancé des outils théoriques développés dans le champ féministe et des transformations de la pratique militante que les auteures analysent à quatre moments précis : la lutte pour l'avortement libre et gratuit dans les années 1970 et 1980, la Coalition «Avortons leur congrès!» en 2005, le renouvellement en cours du cadre théorique de la Fédération du Québec pour le planning des naissances et le collectif La Riposte féministe (2016).
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; avortement; canada; droits des femmes*; histoire et politique; intersectionnalité; inégalités; justice reproductive; justice sociale; militance; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques

Radical reproductive justice: Foundation, theory, practice - Ross, Loretta; Roberts, Lynn; Derkas, Erika; Peoples, Whitney; Bridgewater Toure, Pamela (Feminist press, 2017)
Expanding the social justice discourse surrounding "reproductive rights" to include issues of environmental justice, incarceration, poverty, disability, and more, this crucial anthology explores the practical applications for activist thought migrating from the community into the academy. Radical Reproductive Justice assembles two decades’ of work initiated by SisterSong Women of Color Health Collective, creators of the human rights-based “reproductive justice” framework to move beyond polarized pro-choice/pro-life debates. Rooted in Black feminism and built on intersecting identities, this revolutionary framework asserts a woman's right to have children, to not have children, and to parent and provide for the children they have.
Keywords: afro-féminisme; approches et analyses; discipline; droit; droits des femmes*; intersectionnalité; justice reproductive; justice sociale; maternité; militance; santé; science politique et droit; sciences humaines; sociologie; thématiques

Undivided rights: Women of color organizing for reproductive justice - Silliman, Jael; Fried, Marlene Gerber; Ross, Loretta; Gutiérrez, Elena (Haymarket Books, 2016)
Undivided Rights captures the evolving and largely unknown activist history of women of color organizing for reproductive justice—on their own behalf.Undivided Rights presents a textured understanding of the reproductive rights movement by placing the experiences, priorities, and activism of women of color in the foreground. Using historical research, original organizational case studies, and personal interviews, the authors illuminate how women of color have led the fight to control their own bodies and reproductive destinies. Undivided Rights shows how women of color—-starting within their own Latina, African American, Native American, and Asian American communities—have resisted coercion of their reproductive abilities. Projected against the backdrop of the mainstream pro-choice movement and radical right agendas, these dynamic case studies feature the groundbreaking work being done by health and reproductive rights organizations led by women-of-color.The book details how and why these women have defined and implemented expansive reproductive health agendas that reject legalistic remedies and seek instead to address the wider needs of their communities. It stresses the urgency for innovative strategies that push beyond the traditional base and goals of the mainstream pro-choice movement—strategies that are broadly inclusive while being specific, strategies that speak to all women by speaking to each woman. While the authors raise tough questions about inclusion, identity politics, and the future of women’s organizing, they also offer a way out of the limiting focus on "choice."Undivided Rights articulates a holistic vision for reproductive freedom. It refuses to allow our human rights to be divvied up and parceled out into isolated boxes that people are then forced to pick and choose among.
Keywords: afro-féminisme; amériques; approches et analyses; discours dominant; droits des femmes*; histoire et politique; intersectionnalité; inégalités; justice reproductive; militance; régions géographiques; sofia; système colonial; systèmes d'oppressions; thématiques; états-unis

The color of violence: The incite! anthology - INCITE! Women of Color Against Violence (Duke University Press, 2016)
The editors and contributors to Color of Violence ask: What would it take to end violence against women of color? Presenting the fierce and vital writing of organizers, lawyers, scholars, poets, and policy makers, Color of Violence radically repositions the antiviolence movement by putting women of color at its center. The contributors shift the focus from domestic violence and sexual assault and map innovative strategies of movement building and resistance used by women of color around the world. The volume's thirty pieces—which include poems, short essays, position papers, letters, and personal reflections—cover violence against women of color in its myriad forms, manifestations, and settings, while identifying the links between gender, militarism, reproductive and economic violence, prisons and policing, colonialism, and war. At a time of heightened state surveillance and repression of people of color, Color of Violence is an essential intervention.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; droits des femmes*; femmes* autochtones; femmes* de couleur; femmes* immigrantes; hétérosexisme; intersectionnalité; justice reproductive; justice sociale; militance; outils; ouvrages de références; périodes historiques; racisme; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Advocating from the margins: The reproductive justice movement and the politics of oppositional consciousness - Kirwood, Zachary (Wesleyan University, 2012)
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; droits des femmes*; histoire et politique; intersectionnalité; justice reproductive; mémoires/thèses; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; états-unis; étude qualitative

A call to incorporate a reproductive justice agenda into reproductive health clinical practice and policy - Gilliam, Melissa L.; Neustadt, Amy; Gordon, Rivka (Contraception, 2009)
Keywords: approches et analyses; contraception; discipline; droits des femmes*; intersectionnalité; inégalités; justice reproductive; justice sociale; médecine; ressource en ligne; santé; santé des femmes*; sciences; sciences humaines; sexologie; systèmes d'oppressions; thématiques

Les tactiques féministes confrontées aux « tirs amis » dans le mouvement des femmes en Irlande - Taylor, Judith (Politix, 2007)
Cet article examine les modèles courants d’intelligibilité de l’interaction tactique entre les acteurs des mouvements sociaux et montre leur insuffisance pour rendre compte de l’invention tactique dont a dû faire preuve le mouvement des femmes en Irlande. Une analyse des efforts déployés par les féministes irlandaises pour l’extension du droit à l’avortement met en question l’idée que les innovations tactiques ne répondraient qu’aux contre-mouvements ou à la répression de l’État. L’expression « tir ami » fait référence au processus par lequel des groupes qui ne sont pas en opposition avec un mouvement, mais qui n’en font pas non plus partie, constituent une menace pour les finalités de ce mouvement. L’observation de la campagne féministe, de ses meetings et de l’ensemble de sa mise en scène politique donne des aperçus significatifs sur les effets des tirs amis et, spécifiquement, sur le rôle des hommes dans les mouvements de femmes.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; avortement; care; corps; cours; discipline; droits des femmes*; europe; intersectionnalité; irlande; justice reproductive; justice sociale; pol5185; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques

Avortement : un pays pas comme les autres - Harrison-Julien, Pasquale
L’avortement au Canada est une réalité complexe et souvent méconnue. De la Gaspésie au Nunavik, en passant par les provinces de l'Atlantique et les grandes villes, la série balado Avortement : un pays pas comme les autres met en lumière les disparités régionales et les obstacles rencontrés par les Canadiennes désirant avoir recours à ce soin de santé. La journaliste Pasquale Harrison-Julien aborde des sujets délicats tels que les avortements après le premier trimestre, les pressions culturelles et familiales, et les implications politiques et sociales des lois sur l'avortement. À travers des témoignages poignants et des entretiens avec des experts, des militants et des médecins, découvrez les histoires de femmes qui ont dû naviguer dans un système de santé inégal pour exercer leur droit dans ce balado essentiel pour comprendre les enjeux actuels et futurs de la santé reproductive au Canada.
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; avortement; canada; communication; cours; discipline; droits des femmes*; intersectionnalité; journalisme; justice reproductive; patriarcat; pol4102; premier cycle; périodes historiques; régions géographiques; santé; sexisme; système colonial; systèmes d'oppressions; thématiques